Modeling and Analysis of a Tractor Diesel Engine Test Stand Structure Using the Finite Element Method - Mohammad Mohammadi; Seyed Mohammad Reza Nazemosadat; Ahmad Afsari (Biomechanism and Bioenergy Research)
The Diesel Engine Test Stand Structure (DETSS) is crucial in industries like automotive, agriculture, shipbuilding, military, and aerospace for engine testing and repair, ensuring safety for technicians. This study designed a steel structure in INVENTOR software, considering the engine's weight, power, and torque. Static and dynamic analyses were conducted using ABAQUS. Static analysis revealed maximum von Mises stress (300–617 MPa) in the motor mount and chassis and minimum stress (100–175 MPa) in the radiator mount, fuel tank, and control panel. Vibrational analysis showed maximum displacement (0.08 mm at 7.20 Hz) in the chassis and mounts, and minimum displacement (0.05 mm at 9.45 Hz) in the control panel, fuel tank, and battery holder. The findings highlight the need for reinforcement and optimization of the motor mount and engine holder.